THE FIRST EARLY CHRISTIAN TESTIMONIES OF CHRISTMAS - Naumowicz, ks. Józef (Colloquia Litteraria, 2019)
The article presents the earliest reference to the celebration of Christmas as a holiday or feast, namely: the Roman calendar of Philocalus (so-called Chronography of 354), the first sermons preached for this occasion (pope Liberius, Optate from Milewe, Zenon from Verona) and the first hymns (Ambrose from Milan and Prudentius, Ephrem the Syrian). The analysis of sources shows that there is no record of this feast before the First Council at Nicaea (325 A.D.). It appeared in Rome around 335 A.D. and from there it has spread to other regions. As soon as it appeared, it quickly gained popularity and characteristic theological significance.